Synthesis of Complex Compounds of Cr(III) Metal Ions and Their Application as Fluorosensors of Pb(II) and Cu(II) in Laboratory Waste - Syahputri, Yulian; Sutanto, Sutanto; Kusumawardani, Linda Jati; Saputra, Muhammad Rizki (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2025)
Indonesia's exposure of lead (Pb) and copper (Cu) heavy metal ions to humans and the environment has received increased attention over the past few decades as a result of the increasing application of heavy metals in various industries and transportation. Complex compounds of Cr3+ sensors with fluorescence-based pyrazoline-derived ligands (fluorosensors) have the potential to detect Pb2+ and Cu2+ heavy metal ions. The purpose of this study is to synthesize complex compounds of Cr3+ ions with pyrazoline-derived ligands and its potential as a fluorescence-based sensor of Pb2+ and Cu2+ heavy metal ions. Complex compounds formed are characterized and fluorosensor study by spectroscopic methods. The results showed that the synthesis of complex compounds was successfully carried out and a brown precipitate with a melting point of 253.2°C was obtained. Based on the results of the characterization of complex compounds of Cr3+ metal ions with pyrazolin-derived ligands using a UV-Vis spectrophotometer, two absorption peaks were obtained at 226 and 370 nm, two peaks indicating the presence of transition types π→π* and n→π*. The fluorescence spectrophotometer results showed two emission peaks, the peak absorption maximum of Cr3+ complex compounds was in the region 491 nm with a fluorescence intensity of 320.40 a.u. The determination of the fluorosensor potential of Cr3+ complex compounds with the addition of Pb2+ and Cu2+ metal ions showed significant changes in fluorescence so that fluorosensor types were obtained for Cr3+ metal ion complex compounds with Pb2+ and Cu2+, namely